Sosiologi Sastra dan Nilai Pendidikan Karakter Cerita Rakyat Watu Ulo: Bahasa Indonesia - Riska Fita Lestari; Lutfi Irawan Rahmat (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Literary works that can be used as a resource to broaden horizons and instill ethical values in readers are folklore. as an effort to support the dissemination and preservation of regional literature. Seta wants to find out about the sociological structure of literature and the value of character education in the folklore of Watu Ulo in Jember Regency. This study uses a qualitative, descriptive type of method with a sociology of literature approach and character education values. The data from this study are verbal, namely planners, implementers, data collectors, analyzers, data interpreters, from character statements in the form of dialogues or monologues, as well as narrations contained in watu ulo folklore. The purpose of the qualitative method is so that the writer can get to know history more deeply about the research environment by using descriptive research types, in the sense that researchers are trying to find evidence experienced in formal reasoning. The data obtained in this study are data from the Ambulu community on sociological values and character education. expression of events that have been framed in patterns creatively and imaginatively. With literary works, conditions are often known—snippets of people's lives as experienced, observed, captured, and designed by the author. Literature and society are closely related because, basically, the existence of literature often stems from problems in humans and their environment. Socio-cultural manifestations and character education values in folklore.